2017
DOI: 10.3390/catal7080237
|View full text |Cite
|
Sign up to set email alerts
|

Facile, One-Pot, Two-Step, Strategy for the Production of Potential Bio-Diesel Candidates from Fructose

Abstract: Abstract:The production of bio-diesel fuels from carbohydrates is a promising alternative to fossil fuels with regard to the growing severity of the environmental problem and energy crisis. Potential bio-diesel candidates or additives, such as 5-(hydroxymethyl)-2-(dimethoxymethyl) furan (HDMF), 2-(dimethoxymethyl)-5-(methoxymethyl) furan (DMMF), and 5-(methoxymethyl)-2-furaldehyde (MMF) could be produced from the alcoholic solutions of both 5-HMF and fructose in the presence of solid acid catalysts. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…37,38 Figure 4B showed that HMF was completely converted at 8 h, and the maximum MMF yield of 91.5% was reached at 6 h. The dehydration reaction of fructose and the etherification reaction of HMF are both first-order kinetics reactions. 22,31 The latter rate constants k value (0.88 h −1 ) is considerably less than that of the former (8.51 h −1 ), and the corresponding activation energies are 42.6 and 21.4 kJ/mol (see Tables S1−S3 and Figures S3 and S4), respectively, indicating that the second step was the rate-determining step. To speed up the second step reaction and thus shorten the reaction time, a series of experiments under higher reaction temperatures were conducted (see Figure S5).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…37,38 Figure 4B showed that HMF was completely converted at 8 h, and the maximum MMF yield of 91.5% was reached at 6 h. The dehydration reaction of fructose and the etherification reaction of HMF are both first-order kinetics reactions. 22,31 The latter rate constants k value (0.88 h −1 ) is considerably less than that of the former (8.51 h −1 ), and the corresponding activation energies are 42.6 and 21.4 kJ/mol (see Tables S1−S3 and Figures S3 and S4), respectively, indicating that the second step was the rate-determining step. To speed up the second step reaction and thus shorten the reaction time, a series of experiments under higher reaction temperatures were conducted (see Figure S5).…”
Section: Resultsmentioning
confidence: 91%
“…Zhu et al reported that 47 mol % MMF was obtained from fructose with Amberlyst-15 in tetrahydrofuran/methanol mixed solvent under 120 °C for 3 h. Kraus and Guney introduced hexane to assist sulfonic acid functionalized ionic liquids to increase MMF yield under 100 °C for 20 min. Qiu et al employed DMSO, SiO 2 –HNO 3 , and methanol to obtain 25 mol % MMF yield at 150 °C for 2 h. However, the highest MMF yield reported in these references is only 57 mol %, which could be ascribed to the weak performance of cosolvent with acid catalyst, the short reaction time, and/or the high reaction temperature. Moreover, the lack of detailed studies about the reaction mechanism of fructose conversion to MMF also impeded the achievement of a high MMF yield, because a clear reaction mechanism plays a vital role in catalyst screen and design, reaction medium selection, and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination between this enol and Al 3+ may increase the stability of the former 65 and further aid its cyclization into a five-membered precursor, which is converted into 5-(hydroxymethyl)-2-(dimethoxymethyl)furan (HDMF) through the elimination of two water molecules over the B acid. Subsequently, HDMF undergoes etherification and deacetalization to yield 5-MMF, 66,67 which is finally transformed into ML and methyl formate. 33 These steps are favored in the presence of strong B acids.…”
Section: Intermediates Formed During Methanolysismentioning
confidence: 99%
“…To simplify processing, cascade reactions for the synthesis of biofuels from carbohydrates may also be performed in one-pot as demonstrated for the production of 5-(hydroxymethyl)-2-(dimethoxymethyl)furan from fructose via a two-step dehydration/acetalization process using a facile catalyst SiO 2 -HNO 3 and DMSOmethanol biphasic solvent system [12]. However, even more desirable is to operate continuous-flow reactions, which are often preferred for industrial applications.…”
Section: New Reaction Strategiesmentioning
confidence: 99%